Electrical resistivity and ultrasonic measurements during sequential fracture test of cementitious composite (Fracture and Structural Integrity, 2014)
Cracks in cover of reinforced and pre-stressed concrete structures significantly influence the ingress of deleterious species causing decrease in durability of these structures. The paper is focused on the effect of fracture process on two selected physical parameters of concrete – the electrical resistivity and the ultrasonic pulse passing time – which might be employed as the quality indicator of concrete cover within (nondestructive) procedure(s) of assessment of the structural durability. The concrete electrical resistivity and ultrasonic passing time were investigated here with respect to two variants of treatment of the test specimens’ surface (the pre-dried surface and the wet surface). Test configuration of three-point bending of notched beam was utilized to control the crack propagation; the fracture process passed through several loading–unloading sequences between which the electrical resistivity and ultrasonic passing time readings over the fractured region were performed. Equivalent elastic crack model was used for estimation of the fracture advance (described via the effective crack length) at the loading stages corresponding to the resistivity and ultrasonic measurements. Relationships between changes of both the concrete resistivity and ultrasonic pulse passing time and the effective crack length is determined and discussed.
Keywords: Cementitious composite